Treatment of Colored Effluents From Paja Toquilla Dyeing Through an Optimized Fenton Process: Fenton para aguas coloreadas - Echeverría-Paredes, Paulina; Orellana-Iñiguez, Johanna; Tonon, María Dolores; Pinos Velez, Veronica (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In Ecuador, making products of “paja toquilla” has become a referent of the country´s exports. To dye, these productos, aniline dyes are used, and the effluents of these processes are discharged to rivers without treatment. This investigation explores a process for color removal. The first stage involved the determination of the optimal relation between Fe2+ y H2O2 for a Fenton process using an experimental factorial design (32). The best result was reported with the higher and medium levels of FeSO4.7H2O and H2O2 at 30%v/v, respectively. The Fenton process designed was applied to treat solutions of three aniline dyes: blue, red and, black which are the most used in paja toquilla dyeing. For each dye, the percentage of removal and the kinetics were determined, in all cases was above 90% and of second order. Finally, the effluents were neutralized to assess their ecotoxicity with Daphnia Magna, which demonstrated that the effluent could be discharged without aquatic ecotoxicity after the applied process.